Body dysmorphic disorder among dermatologic patients: Prevalence and clinical features - Conrado, Luciana Archetti; Hounie, Ana Gabriela; Diniz, Juliana Belo; Fossaluza, Victor; Torres, Albina Rodrigues [UNESP]; Miguel, Euripedes Constantino; Rivitti, Evandro Ararigboia (Mosby-elsevier, 2010)
Background: An impairing preoccupation with a nonexistent or slight defect in appearance is the core symptom of body dysmorphic disorder (ODD), a psychiatric condition common in dermatology settings.Objective: We sought to determine the prevalence of ODD in dermatologic patients, comparing general and cosmetic settings, and describing some demographic and clinical characteristics.Methods: In all, 300 patients were consecutively assessed. Screening and diagnoses were performed with validated instruments plus a best estimate diagnosis procedure. The final sample comprised 150 patients in the cosmetic group, 150 patients in the general dermatology group, and 50 control subjects. Standard statistical analyses were performed (chi(2), nonparametric tests, logistic regression).Results: The current prevalence was higher in the cosmetic group (14.0%) compared with general (6.7%) and control (2.0%) groups. No patient had a previous diagnosis. Frequently the reason for seeking dermatologic treatment was not the main ODD preoccupation. Patients with ODD from the cosmetic group were in general unsatisfied with the results of dermatologic treatments.Limitations: Cross-sectional study conducted in a university hospital is a limitation. It is uncertain if the findings can be generalized. Retrospective data regarding previous treatments are not free from bias.Conclusions: BUD is relatively common in a dermatologic setting, especially among patients seeking cosmetic treatments. These patients have some different features compared with general dermatology patients. Dermatologists should be aware of the clinical characteristics of ODD to identify and refer these patients to mental health professionals. (J Am Acad Dermatol 2010;63:235-43.)
Keywords: body dysmorphic disorder; body image; body image dissatisfaction; cosmetic procedures; cosmetic treatments: dermatologic symptoms